2020
DOI: 10.1253/circrep.cr-20-0009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Short Stature and Growth Hormone Deficiency and Factors Associated With Short Stature After Fontan Surgery

Abstract: Background: Fontan circulation is characterized by many features commonly observed in heart failure that may affect physical growth regardless of pituitary gland dysfunction status. The aims of the present study were to investigate the prevalence of short stature and growth hormone deficiency (GHD) and determine the factors associated with short stature after Fontan surgery. Methods and Results: On retrospective evaluation of 47 patients after Fontan surgery, a very high prevalence of short stature was observe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…This is especially relevant in children with a Fontan circulation who may have numerous risk factors for poor growth including hypoxemia, relatively low cardiac output, poor nutrition, and nitrogen-depleting conditions such as the complication of protein-losing enteropathy (PLE). Studies have shown a higher prevalence of short stature in children and adolescents after Fontan compared to the general population [ 18 20 ]. Even though, on average, the height deficits post-Fontan are mild, there are subgroups at higher risk for more severe growth problems and it is in these cases where a timely intervention is mandatory to investigate comorbidities and allow time for catch-up growth.…”
Section: The Multidisciplinary Approach: Areas Of Focusmentioning
confidence: 99%
“…This is especially relevant in children with a Fontan circulation who may have numerous risk factors for poor growth including hypoxemia, relatively low cardiac output, poor nutrition, and nitrogen-depleting conditions such as the complication of protein-losing enteropathy (PLE). Studies have shown a higher prevalence of short stature in children and adolescents after Fontan compared to the general population [ 18 20 ]. Even though, on average, the height deficits post-Fontan are mild, there are subgroups at higher risk for more severe growth problems and it is in these cases where a timely intervention is mandatory to investigate comorbidities and allow time for catch-up growth.…”
Section: The Multidisciplinary Approach: Areas Of Focusmentioning
confidence: 99%
“…Alteration in this mechanism may be implicated in the high incidence of short stature seen in Fontan populations. 3,6 TRH triggers thyroid-stimulating hormone (TSH) production by the anterior pituitary gland; this system may be involved in the high incidence of hypothyroidism as well as short stature in Fontan populations. 3,4,6 Gonadotropin-releasing hormone (GnRH) neurons are found in the medial preoptic nucleus (in the anterior superior subunit) and in the arcuate nucleus.…”
Section: Discussionmentioning
confidence: 99%
“…3,6 TRH triggers thyroid-stimulating hormone (TSH) production by the anterior pituitary gland; this system may be involved in the high incidence of hypothyroidism as well as short stature in Fontan populations. 3,4,6 Gonadotropin-releasing hormone (GnRH) neurons are found in the medial preoptic nucleus (in the anterior superior subunit) and in the arcuate nucleus. These trigger follicular stimulating hormone (FSH) and luteinizing hormone (LH) production by the anterior pituitary gland via the portal circulation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation